2021
DOI: 10.1016/j.jinf.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of SARS-CoV-2 RNA polymerase chain reaction using a clinical and radiological reference standard

Abstract: Objectives Diagnostic tests for SARS-CoV-2 are important for epidemiology, clinical management, and infection control. Limitations of oro-nasopharyngeal real-time PCR sensitivity have been described based on comparisons of single tests with repeated sampling. We assessed SARS-CoV-2 PCR clinical sensitivity using a clinical and radiological reference standard. Methods Between March-May 2020, 2060 patients underwent thoracic imaging and SARS-CoV-2 PCR testing. Imaging was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, the studies representing larger populations demonstrated means similar those identified in our review ( Buonafine et al, 2020 ;Xia et al, 2020 ;Chen et al, 2021 ;Flores-Silva et al, 2021 ;Gu et al, 2021 ;Ji et al, 2021 ;Stockdale et al, 2021 ;˙I ¸s lek and Balcı, 2022 ). A cross-sectional study of 1072 patients ( Flores-Silva et al, 2021 ) found that the median time from symptom onset to diagnosis was 7 days, but the time varied from 6 to 10 days.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the studies representing larger populations demonstrated means similar those identified in our review ( Buonafine et al, 2020 ;Xia et al, 2020 ;Chen et al, 2021 ;Flores-Silva et al, 2021 ;Gu et al, 2021 ;Ji et al, 2021 ;Stockdale et al, 2021 ;˙I ¸s lek and Balcı, 2022 ). A cross-sectional study of 1072 patients ( Flores-Silva et al, 2021 ) found that the median time from symptom onset to diagnosis was 7 days, but the time varied from 6 to 10 days.…”
Section: Discussionsupporting
confidence: 84%
“…Another possibility for a non-causal negative association between smoking and COVID-19 diagnoses may be a relatively lower sensitivity of the test of choice (SARS-CoV-2 RNA polymerase chain reaction) among current smokers 31 .…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 RNA test is the golden standard and the most commonly used method for diagnosing COVID-19 across guidelines and regulations, and in this study, all suspected cases and the contacts immediately underwent SARS-CoV-2 RNA testing by rRT-PCR assays of respiratory (throat swab and sputum) specimens, which are the most commonly recommended specimens across guidelines and regulations and which are more easily obtainable and more practicable. A Finland population-based study showed that the clinical sensitivity of SARS-CoV-2 RT-PCR testing was only moderate at best, with relatively high false-negative rates (26), and a single swab test might not be sufficient (27); the sensitivity was even lower among smokers (28). Test sensitivity increased with more test times, and were 72.4, 89.8, 97.3, and 100.0% for the first, second, third, and seventh tests, respectively (22).…”
Section: Discussionmentioning
confidence: 99%